1997
DOI: 10.1046/j.1365-2222.1997.d01-559.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of peanut allergy

Abstract: Peanut allergy is characterized by more severe symptoms than other food allergies and by high rates of symptoms on minimal contact. Skin-prick testing and peanut-specific IgE levels do not predict clinical severity. Avoidance of peanut is difficult. Many people suffering severe relations are inadequately treated. Sufferers need education and training in the use of rescue medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 4 publications
2
84
0
Order By: Relevance
“…Peanut allergy frequently becomes manifest early in life and, in more than 74% of cases, following the first oral exposure to peanuts [12,13]. This observation has led to an investigation of other possible routes of first exposure (and thus, sensitization), including in utero, via breast milk, and via exogenous application of peanut-protein containing oils, especially to disrupted skin [14][15][16].…”
Section: Introductionmentioning
confidence: 96%
“…Peanut allergy frequently becomes manifest early in life and, in more than 74% of cases, following the first oral exposure to peanuts [12,13]. This observation has led to an investigation of other possible routes of first exposure (and thus, sensitization), including in utero, via breast milk, and via exogenous application of peanut-protein containing oils, especially to disrupted skin [14][15][16].…”
Section: Introductionmentioning
confidence: 96%
“…The allergy to peanut is characterized by more severe symptoms than other food allergies and by a high rate of symptoms on minimal contact [3,4]. The incidence of peanut, and food allergies in general, has increased in the recent decades.…”
Section: Introductionmentioning
confidence: 99%
“…However, 72% to 81% of presentations of PA occur on first known exposure to peanut. [2][3][4] Public health measures to prevent peanut and other food allergies in the United States and United Kingdom (UK) have focused on allergen exclusion by the mother during pregnancy and lactation, and by the child in the first 3 years of life. 5,6 Despite this advice, there is evidence to suggest that PA continues to rise in these countries, 7 and randomized interventional studies have not shown an effect on preventing PA by avoiding ingestion during gestation, lactation, or infancy.…”
mentioning
confidence: 99%